Repercussions of the HIV virus in HIV-positive pregnant women and the challenges faced by them: a literature review (Research, Society and Development, 2023)
HIV is a retrovirus with tropism for CD4+ T lymphocytes, cells of the immune system responsible for coordinating the immune response to infection. HIV-positive pregnant women share the fear of social judgment, which makes it difficult to start treatment and increases the risks of vertical transmission. The objective of this work is to investigate the repercussions of the HIV virus in seropositive pregnant women and antiretroviral therapy, and the factors related to therapeutic adherence and vertical transmission, considering lifestyle and biopsychosocial habits. The methodology consists of an integrative review of qualitative literature on the biopsychosocial repercussions of HIV infection in pregnant women. The descriptors “gestation” was crossed; “HIV”; “antiretroviral therapy”; "treatment"; in the following databases: Virtual Health Library (VHL); National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO) and EbscoHost. Pregnancy, with the presence of HIV, poses several challenges to women, among which efforts aimed at preventing mother-to-child transmission of the virus stand out. In addition, prior HIV infection or during pregnancy is a risk factor for pregnancy complications and, therefore, must be addressed at all stages of pregnancy. The challenges faced by these pregnant women go beyond pathophysiological barriers. The vertical transmission of HIV has severe consequences for the mother and child, involving risks of malformation and miscarriage; coverage of outpatient screening is critical to the progress of pregnancy.